2018
DOI: 10.1017/s1742170518000364
|View full text |Cite
|
Sign up to set email alerts
|

A modified choice experiment to examine willingness to participate in a Community Supported Agriculture (CSA) program among low-income parents

Abstract: There is a need to improve geographical and financial access to healthy foods for limited resource populations in rural areas. Community Supported Agriculture (CSA) programs can improve access to healthy foods in rural and limited-resource populations. However, research is needed to discern the most appealing conditions for a CSA (e.g. price, frequency, food quantity) among rural, low-income customers. The goal of this study was to understand low-income consumers' preferences related to participation in a CSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…Our study was not designed to ascertain how these factors might influence participation among prospective and former CSA members, but this is an important area of inquiry. Prior studies have found that CSA price is a key factor for participation [16,25,33,47], particularly for lower income households [28,45]. However, competing on price may not be practical, considering the low profit margins in CSA [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was not designed to ascertain how these factors might influence participation among prospective and former CSA members, but this is an important area of inquiry. Prior studies have found that CSA price is a key factor for participation [16,25,33,47], particularly for lower income households [28,45]. However, competing on price may not be practical, considering the low profit margins in CSA [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…We also asked participants to select preferred produce items from a list of 32 vegetables and fruits typically produced in the study regions, and to report the quantities they desired. Further detail on the scenarios (as used with a different population) is available elsewhere [45].…”
Section: Study Participants and Data Collectionmentioning
confidence: 99%
“…This is the case in the United States (US), where the Supplemental Nutrition Assistance Program Electronic Benefit Transfer (SNAP/EBT) provides economic support by making local food more affordable. Healthy food accessibility for low-income population was analyzed in various past studies, focusing on retailing [31][32][33] and on CSA [20,[34][35][36][37][38][39]. Although studies on retailing mostly explore food economic affordability and physical accessibility to healthy food, research on alternative food networks highlight the importance of the social, community, and networking aspects of consumers' approach to healthy food.…”
Section: Csa Farmers' Motivations and Expectationsmentioning
confidence: 99%
“…Recruiting CSA members [6,7,18,29,38,39,44,57,62,82,84] Communicating with CSA members [17,64,75] Communicating easily with all members [75] Environmental drawbacks Farm management caused by the weather [58] Farm management caused by pests and diseases [26,58] Farm management due to weed control [26] Difficulties in growing product without chemical pesticide and herbicide [26] Table A2. The US versus HU farmers' characteristics (Chi-square analysis).…”
Section: Benefits (Benefits In)mentioning
confidence: 99%
“…Selecting consumer-friendly hours of operation and pickup locations facilitates motivation to purchase from DTC venues [10]. For example, a recent modified choice experiment found that low-income consumers would be less interested in trying a CSA if the distance from their home to the pickup site was about the same as the distance to supermarket, unless the CSA offered significant cost savings [23]. Yet if the pickup site is too far from the farm, or outside established delivery routes, extra driving time and fuel costs cut into farmer profit [14].…”
Section: Introductionmentioning
confidence: 99%